First insights into herbivore–plant interaction of the spurge hawkmoth and Euphorbia cyparissias - Fiedler, Stephanie; Langner, Mathias; Oertel, Reinhard; Vassão, Daniel G.; Nitschke, Julia; Gershenzon, Jonathan; Hundsdoerfer, Anna K. (Frontiers in Ecology and Evolution, 2023)
The spurge hawkmoth Hyles euphorbiae (Lepidoptera, Sphingidae) is an insect herbivore feeding exclusively on spurges (Euphorbia). These are toxic due to their secondary metabolites including diterpene esters with numerous harmful biological activities, preventing their use by most herbivores. Extracts of frass from H. euphorbiae and of its main larval food plant in Central Europe, the cypress spurge (Euphorbia cyparissias L.), were analyzed via liquid chromatography using a triple-quadrupole (MS/MS) and a high-resolution–quadrupole time-of-flight mass spectrometer (QTOF-MS). We report for the first time the finding of the tigliane (phorbol ester) phorbol-13-acetate and two 12-O-tetradecanoylphorbol-13-acetate (TPA) isomers of unknown structure (compounds 2 and 3) in E. cyparissias. Our data support the assignment of these two compounds as tiglianes and are therefore referred to by us as “putative tiglianes”. Additionally, the distribution of the three reported compounds within the plant parts (leaves, stem and root) was analyzed to gain first insights into the metabolite conditions H. euphorbiae copes with in nature. Phorbol-13-acetate was detected in the plant’s root only, while the other compounds were observed in all three plant parts, although in different distributions. Moreover, our results indicate that the occurrence of compound 3 rises upon larval feeding. Finally, the presence of the plant-derived putative tiglianes in frass from E. cyparissias leaves feeding larvae is confirmed, corroborating the close plant–herbivore interaction.